Model en werkwyse by literatuurondersoek – Beredeneer en toegepas op Drie kaal koppe eet tesame (Jan Rabie) - Steenberg, D. H. (Koers, 1984)
The point is made unequivocally that a scientist cannot work with a model and a method of science uncritically derived from somebody else.